Activation of Hypoxia‐Inducible Factor‐2 in Adipocytes Results in Pathological Cardiac Hypertrophy. Issue 6 (10th December 2013) - Lin, Qun; Huang, Yan; Booth, Carmen J.; Haase, Volker H.; Johnson, Randall S.; Celeste Simon, M.; Giordano, Frank J.; Yun, Zhong
Abstract : Background: Obesity can cause structural and functional abnormalities of the heart via complex but largely undefined mechanisms. Emerging evidence has shown that obesity results in reduced oxygen concentrations, or hypoxia, in adipose tissue. We hypothesized that the adipocyte hypoxia‐signaling pathway plays an essential role in the development of obesity‐associated cardiomyopathy. Methods and Results: Using a mouse model in which the hypoxia‐inducible factor (HIF) pathway is activated by deletion of the von Hippel–Lindau gene specifically in adipocytes, we found that mice with adipocyte–von Hippel–Lindau deletion developed lethal cardiac hypertrophy. HIF activation in adipocytes results in overexpression of key cardiomyopathy‐associated genes in adipose tissue, increased serum levels of several proinflammatory cytokines including interleukin‐1β and monocyte chemotactic protein‐1, and activation of nuclear factor–κB and nuclear factor of activated T cells in the heart. Interestingly, genetic deletion of Hif2a, but not Hif1a, was able to rescue cardiac hypertrophy and abrogate adipose inflammation. Conclusion: We have discovered a previously uncharacterized mechanism underlying a critical and direct role of the adipocyte HIF‐2 transcription factor in the development of adipose inflammation and pathological cardiac hypertrophy.